#TITLE_ALTERNATIVE# - CHANDRA TAMTAMA (NIM 12104005); Pembimbing : Prof. Dr. Ir. Syoni Soepriyanto, M.Sc. dan Dr. A, ADITYA
Pipeline has a significant role in oil and gas industries. Both production and distribution of oil and gas processes in the industry are depended on pipelines. Controls and inspections are needed for the pipelines to guarantee safety for all production and distribution of oil and gas processes. Corrosion is the main caution of failure occurs on all material especially pipelines. It is needed an analytical process to analyze the effect of corrosion occurs to the reliability of pipelines. The analytical process is called corrosion risk base on analytical system which integrated type of corrosion occurs on pipeline and how to handle it well. Failure probability analysis is one of the analytical processes. This analysis consists of a failure probability analytical system on the subsea pipelines from two typical oil and gas industries in Indonesia. Subsea pipelines in this analysis are internally corroded with carbon dioxide (sweet corrosion). Reliability based analytical method is done by several steps, including corrosion identification, corrosion rate calculation, and probability of failure calculation. All subsea pipelines have some operational data results from the inspection. NORSOK model are used in the analysis to predict internal corrosion rate occurs on the pipeline. Corrosion rate then will be transferred into a calculation using First Order Second Moment (FOSM) method to obtain probability of failure. Probability of failure from analyzed pipeline each year will be plotted into matrix based on standard that will describe the critically level of pipelines for each year. The critically of pipelines can conclude that the pipelines are in either safe or failed. Results from NORSOK model give the corrosion rate of 22 analyzed pipelines between 0.151-0.407 mm/year. Inhibitor injection was also calculated in this analysis with all inhibitor efficiency is 70% and results the corrosion rate between 0.04-0.112 mm/year. The injection rates are between 0.01-17 MSCFD depended on the gas flow rate and amount of standard that must be added. Pipeline 16 OD-Z-X52 is analyzed using FOSM (First Order Second Moment) method to results its probability of failure each year. The reliability of this pipeline will be decreased as the probability of failure increased by the time 2020. At that time pipeline is categorized on very high risk of failure.